PENGARUH FASILITAS KANTOR, KUALITAS PELAYANAN DAN STANDAR OPERASIONAL PROSEDUR TERHADAP TINGKAT KEPUASAN PENGUNJUNG PADA DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH KABUPATEN BATANGHARI - Ratna Ratna; Endang Meiliani (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
This study uses primary data obtained by distributing question naires to visitors Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari. The population of this study amounted to 1,029 people with a total sample of 92 respondents. The analytical tool used is the Likert scale and scale range. From the research shows the condition of Office Facilities in the Regional Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari is known as an average index value of 3.63 or categorized as Good, because the Regional Library and Archives Service has training facilities for visitors. From the research shows that Service Quality in the Regional Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari is known as the average index value of 3.62 is in the Good category, because the Regional Library and Archives Service Provides polite and attentive service to visitors. From the study shows the Standard Operating Procedure at the Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari District, it is known that the average index value of 3.61 is in the Good category, because the Regional Library and Archives Service has procedures that are in accordance with the applicable legal basis. From the research shows that the visitors' satisfaction at the Dinas Perpustakaan dan Kearsipan Daerah Kabupaten Batang Hari is known as the average index value of 3.68 is in the Good category, because the visitors of the Regional Library and Archives Service are satisfied with the real, trusted, responsive, polite and confident services give it